Pentingnya Ibadah Keluarga dalam Mengabarkan Injil di GMIM - Walalangi, Winda Lystia (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2020)
The reality that exists within the scope of GMIM's ministry is that there are still those who override the importance of the gospel being preached as a power of faith for all family members and that starts from family worship as a forum to accommodate every personal and family struggle, and build personal relationships with God and fellow family members. Therefore, an openness is needed for each family member so that the life that God wants becomes even more real to witness to many people in the preaching of the gospel.